PENGARUH KOMPENSASI TERHADAP DISIPLIN KERJA PEGAWAI PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN SUMATERA SELATAN - Puput Maretha Sari; Supardi A Bakri; Yuliansyah M Diah (JEMBATAN, 2015)
This study examines the effect of compensation variable towards employees' discipline working in Education Quality Assurance Institutions of South Sumatera. The purpose of this study is to analyze the influence of employees' compensation towards discipline working of Education Quality Assurance Institutions of South Sumatera. The independent variable of this study is compensation and the dependent variable of this study is discipline working. This study uses primary data in the form of a questionnaire given to the respondents. The results of this study shows that the compensation from Education Quality Assurance Institutions of South Sumatera gives effect to employees' working discipline, which is positive correlation between compesation and working discipline.Keywords: compensation, discipline, working